Complications after thigh sarcoma resection. Issue 6 (4th February 2020) - Elswick, Sarah M.; Curiel, Daniel A.; Wu, Peter; Akhavan, Arya; Molinar, Vanessa E.; Mohan, Anita T.; Sim, Frank H.; Martinez‐Jorge, Jorys; Saint‐Cyr, Michel
Abstract: Background and Objectives: Standard treatment for extremity sarcoma is limb‐sparing surgery often with radiation, but complications occur frequently. We sought to determine factors predictive of wound complications after thigh sarcoma resection and reconstruction while analyzing trends over time. Methods: We reviewed all thigh defects requiring plastic surgeon reconstruction following sarcoma resection at our institution from 1997 to 2014. Patient demographics, comorbidities, operative characteristics, multi‐modality therapies, and complications were analyzed. Wound complications were: infection, dehiscence, seroma, hematoma, or partial/total flap loss. Results: There were 159 thigh reconstructions followed for 30 months on average. Eighty‐seven percent of patients underwent radiation and 42% had chemotherapy. Almost half (49.1%) had a complication. The most common wound complication was surgical site infection (23.3%) followed by dehiscence (19.5%), and seroma (10.7%). Less common were partial (2.5%) or total flap loss (0.6%). Reoperation was required in 21 patients (13.2%). Tobacco use, older patient age, cardiac disease, and higher body mass index were independently associated with wound complications. Complications trended towards decreasing over time, but this was not statistically significant. Conclusions: Tobacco use, cardiac disease, and higher body mass index, but not the timing of reconstruction, appear to increase the risk of wound complications after thigh soft tissue sarcomas resection and plastic surgery reconstruction.